Information Management in Multicenter Studies: the Brazilian Longitudinal Study for Adult Health - Duncan, Bruce Bartholow; Vigo, Alvaro; Hernandez, Emerson; Luft, Vivian Cristine; Ahlert, Hubert; Bergmann, Kaiser; Mota, Eduardo (Revista de Saúde Pública, 2013)
Information management in large multicenter studies requires a specialized approach. The Estudo Longitudinal da Saúde do Adulto (ELSA-Brasil - Brazilian Longitudinal Study for Adult Health) has created a Datacenter to enter and manage its data system. The aim of this paper is to describe the steps involved, including the information entry, transmission and management methods. A web system was developed in order to allow, in a safe and confidential way, online data entry, checking and editing, as well as the incorporation of data collected on paper. Additionally, a Picture Archiving and Communication System was implemented and customized for echocardiography and retinography. It stores the images received from the Investigation Centers and makes them available at the Reading Centers. Finally, data extraction and cleaning processes were developed to create databases in formats that enable analyses in multiple statistical packages.